Transduction and feedback regulation in morphodynamic signaling networks - Gierse, Carolin (Technische Universität Dortmund, 2025)
Many fundamental processes in the function of cells and tissues are dependent on dynamic cell shape changes. For example, individual cells must coordinate changes in their shape during tissue morphogenesis or during directional migration in the immune response. These processes have to be coordinated tightly in space and time, and failures in this coordination can contribute to serious diseases, such as cancer metastasis. Previous studies identified a signaling network that generates highly dynamic, oscillatory, mechanosensitive contraction pulses driven by cell contraction master regulator Rho, a small GTPase. These dynamics emerge from a combination of rapid positive and slow negative feedback regulation of Rho. The exact mechanism, how negative feedback is mediated is still unclear. Here, light-induced rapid plasma membrane recruitment of the Myosin II activator ROCK1 induced a strong accumulation of Myosin II at the plasma membrane, and surprisingly also lead to a reduction of actin. This change in the relative abundance of Myosin II vs actin resulted in the inhibition of basal and dynamic Rho activity at the plasma membrane. A detailed analysis of the molecular mechanism by which ROCK1 activates Myosin, revealed a novel Rho binding site at the extreme C-terminus of ROCK1 within its PHC1 domain. Functional investigations demonstrated that the PHC1 domain is indispensable for effective recruitment to active Rho, and that it contributes to the transduction of Rho activity through ROCK1 leading to Myosin II activation. In conclusion, a Myosin II dependent process was identified that mediate negative feedback regulation in the cell contraction network, and novel insights into the regulation of ROCK1 and its mechanism of transducing Rho signals to Myosin II were uncovered. This thesis therefore provides new perspectives on the fundamental process of cell contraction and its regulation and thereby can help to gain a better understanding of the biological processes that are dependent on cell contraction, such as cell migration or tissue morphogenesis.
Keywords: ROCK; Myosin; Contraction; Migration; Cell Biology; System Biology; TIRF; 570; 540; Myosin